BIVOLTINE FOUNDATION CROSSES - THE ONLY RESOURCE OF BIVOLTINE SEED COCOONS UNDER THE TROPICAL CLIMATIC CONDITION OF WEST BENGAL - CHANDA, S.; SAHA, L.M.; KAR, N.B.; BINDROO, B.B. . (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2013)
Production of bivoltine seed cocoons, as a source of bivoltine male moths, in West Bengal is jeopardized for the tropical climatic conditions characterized by high temperature and high humidity from April to September and low temperature with low humidity from October to March. In such circumstances bivoltine foundation crosses (FCs) are the only sustainable source for production of productive and robust bivoltine seed cocoons. Three bivoltine FCs, namely SK6 x SK7, BHR2 x BHR3 and B.Con.1 x B.Con.4 were reared in five seed crop seasons with NB4D2 - the pure bivoltine breed as control, Pooled data of five seed crop seasons, summer (May-June), rainy (July-Aug.), autumn (Sept.-Oct), winter (Nov.-Dec.) and spring (Feb.-Mar.), revealed that the bivoltine FCs recorded higher survillbility percentage ranging from 70.31% to 83.29% (P<0.)5) compared to 58.98% in case NB4D2, Yield/100 DFLs varied significantly (P<0.05) from 39.4.17 kg to 49,130 kg in FCs compared to 33,280 kg in NB4D2. Further, yield/ 100 DFLs of bivoltine seed cocoons in autumn was 43,822 kg, 40,642 kg and 39,417 kg in SK6 x SK7, BHR2 X BHR} and B.Con 1 x B.Con 4, respectively compared to NB4ID2 (30,089 kg). Pupation percentage of all the breeds in five seasons was >90% confirming the sustainable performance for survihility. Concerning shell percentage, filament length and non-breakable filament length in NB4D2 was better compared to hybrids in five seasons except in Summer. Denier showed no significant difference in average performance of five seasons. Comparatively lower shell percentage and reeling parameters of the hybrids than pure bivoltine can be compensated by higher survillbility and yield/100 DFLs and assuring in production of bivoltine seed cocoons in sustained mode.